Mechanistic insights into the anti-aging effects of Crocus sativus in a D-Gal-induced in vitro neural senescence model - Vanessa Castelli; Patrizia Cesare; Erjola Bej; Michele d’Angelo; Anna Rita Volpe (PLoS ONE, 2025)
Background The increasing number of elderly individuals has made age-related disorders a significant health concern. Aging is a natural, progressive and gradual phenomenon that leads to irreversible modifications in all molecules, cells, tissues and organs of an organism. Brain senescence is associated with increased risk of developing various neurological diseases, such as Alzheimer’s disease, Parkinson’s disease, and stroke. Therefore, finding effective strategies to counteract or delay brain senescence is of great importance for improving the quality of life and health span of the elderly population. Previous studies demonstrated that D-galactose is an appropriate agent to induce aging effects in in vivo and in vitro models. Purpose In the present study, we evaluated anti-aging effects of a local Saffron extract (SE from Central Italy) on D-GAL-induced aging model in vitro. Based on promising preliminary results, future studies will focus on testing this specific Crocus sativus stigma preparation in animal models of aging. Methods The potential anti-aging effect was evaluated using assessment of cell proliferation, live-cell cytotoxicity, Beta-Galactosidase (β-GAL), lipid peroxidation, intracellular reactive oxygen species (ROS), advanced glycation end products (AGEs) and malondialdehyde (MDA) levels. Additionally, the effects of SE pretreatment were examined on cell cycle and endoplasmic reticulum stress. Additionally, we employed a novel approach to analyze deeper changes upon saffron extract treatment, which is label-free holotomography. Results Overall, our findings suggested that pretreatment with SE was protective against D-GAL-induced senescence, by counteracting oxidative and endoplasmic reticulum stress and proteins that regulate cell death. Conclusion We obtained interesting results since pre-treatment with SE ameliorated overall condition, and for the first time we observed the strong anti-aging effect of SE not only in term of morphology, but also dynamics and total dry mass of cells. Overall, our work introduces a novel and promising approach to counteract or delay brain senescence, potentially improving the quality of life and health span of the elderly population.